Structural-Parametric Synthesis Robust Flight Control System under Stochastic Disturbances and Inexact Measurements of the System’s State Vector - Азарсков, В. М.; Галагуз, Т. А.; Тунік, А. А. (Problems of Informatization and Control, 2004)
The problem of synthesis of the optimal LQG controller for a system with stochastic disturbances («color noise»-type) and incomplete measurements of the state vector is solved. Then parametric robust optimization of obtained system is conducted to achieve stabilization and acceptable performance for nominal and parametrically disturbed plants using the same controller. Research is performed at the example of the small UAV (Unmanned Aerial Vehicle) flight control system